Entry and Innovation in Vertically Differentiated Markets - Dirk Bergemann; Juuso Valimaki (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1999)
This paper analyzes the optimal entry into experience goods markets with vertically differentiated buyers. We consider the case where the value of the new product is imperfectly know, but common to all buyers (common values) as well as the case where the quality is different across buyers (private values). We distinguish between enw products that are improvements to existing products and new products that are sbustitutes. Different types of products have qualitatively distinct diffusion paths. Improvements are introduced slowly relative to the full information case, while the substitutes are introduced more aggressively. The slow entry strategy is associated with increasing supply and decreasing prices over time. The reverse patterns holds for an aggressive entry strategy. The incentives to innovate display a similar dinstinction. A firm with a currently inferior product opts for a large but risky innovation, whereas a currently superior product chooses a smaller but certain innovation.
Keywords: D81; D83; 330; Experience Goods; Vertical Differentiation; Entry; Innovation